2013
DOI: 10.1111/cas.12068
|View full text |Cite
|
Sign up to set email alerts
|

TIMELESS is overexpressed in lung cancer and its expression correlates with poor patient survival

Abstract: TIMELESS (TIM) is a mammalian homolog of a Drosophila circadian rhythm gene, but its circadian properties in mammals have yet to be determined. TIM appears to be essential for replication protection and genomic stability. Recently, the involvement of TIM in human malignancies has been reported; therefore, we investigated the role of TIM in lung cancer. Microarray expression analysis of lung cancer cell lines showed that TIM expression was elevated 3.7-fold (P < 0.001) in non-small cell lung cancer cell lines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 18 publications
6
45
0
Order By: Relevance
“…Other studies have shown that TIPIN and TIM are under‐expressed in kidney (Mazzoccoli et al., 2012) and pancreatic (Relles et al., 2013) cancers. By contrast, TIM is overexpressed in bladder (Schepeler et al., 2013) and lung (Yoshida et al., 2013) cancers. We found that the levels of TIPIN mRNA and the proliferation marker Ki67 were strongly positively correlated (p < 2.2 × 10 −16 in the entire population; p = 0.008 in TNBC).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that TIPIN and TIM are under‐expressed in kidney (Mazzoccoli et al., 2012) and pancreatic (Relles et al., 2013) cancers. By contrast, TIM is overexpressed in bladder (Schepeler et al., 2013) and lung (Yoshida et al., 2013) cancers. We found that the levels of TIPIN mRNA and the proliferation marker Ki67 were strongly positively correlated (p < 2.2 × 10 −16 in the entire population; p = 0.008 in TNBC).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, timeless gene expression, unlike other circadian clock genes, is observed to be higher in cancer cells and tissue compared to its expression in healthy tissue . Its elevated expression has in fact been proposed to be a poor prognostic marker in certain cancer types .…”
Section: Core Circadian Clock Genes Are Dysregulated In Cancer Cellsmentioning
confidence: 99%
“…Precisely its expression is enhanced in lung cancer cell lines where its knockdown was related to the induction of apoptosis, suppression of proliferation, and clonogenic growth [34]. In surgically resected specimens from 88 consecutive patients, high TIM protein levels as gauged by immunohistochemistry (IHC) correlated with poor overall survival [34,35].…”
Section: Clock Genes and Circadian Regulationmentioning
confidence: 99%